2020
DOI: 10.1111/jfpe.13599
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the process parameters for extruded commercial sinking fish feed with mixed plant protein sources

Abstract: The aim of the investigation was to optimize extrusion process parameters for processing commercial sinking fish feed with mixed plant protein sources in a pilot‐scale twin‐screw extruder equipped with a preconditioner. It has been found out that the bulk density of feed pellets increased with the moisture content in the range of 22–27% (wt), then decreased with the moisture content from 27 to 32%. Meanwhile, increasing moisture content (22–32%) resulted in a decrease of pellet hardness, water solubility, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
5
7
0
2
Order By: Relevance
“…The increase in moisture content resulted in a decrease in bulk density in this study. Consistent with the present study, Wang et al (2021a) reported that the bulk density of commercial sinking fish feed decreased as the moisture content increased from 27% to 32%. Under high temperature and high moisture content conditions, the superheated water in the extruder promoted bubbles formation and decreased the viscosity of the melt, resulting in a decrease in the bulk density (Samray et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in moisture content resulted in a decrease in bulk density in this study. Consistent with the present study, Wang et al (2021a) reported that the bulk density of commercial sinking fish feed decreased as the moisture content increased from 27% to 32%. Under high temperature and high moisture content conditions, the superheated water in the extruder promoted bubbles formation and decreased the viscosity of the melt, resulting in a decrease in the bulk density (Samray et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the hardness of feeds increased with the decrease in moisture content. Consistent with our study, Wang et al (2021a) reported that the moisture content had an adverse effect on the hardness of extruded commercial sinking fish feed. The above discussion mentioned that at high temperatures, the high moisture content could promote extrudate expansion in our study.…”
Section: Discussionsupporting
confidence: 92%
“…According to Riaz (2009), BD of neutral buoyancy pellets ranges from 480 to 520 g/L for freshwater. After considering optimal condition for extrusion mixture with plant‐based feedstuffs, Wang et al (2021) suggested a minimum density of 560 g/L for sinking pellets. On the whole, tinfoil barb diets appeared to be a slow‐sinking extrudate with no marked differences in ER and BD among the pre‐cooked and native starch sources.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last two decades, aquaculture scientists have sought to identify low-cost alternatives to fish meal and fish oil from alternative sources such as plants, microbes, seaweeds, and insects (Belghit et al, 2019;Wang et al, 2021). Feed formulation strategies, nutrient stability, leaching in water, and raw material properties are also limiting factors that affect the nutritional profile of supplemented diets, which in turn affects aquaculture profitability (Draganovic et al, 2011).…”
Section: Introductionmentioning
confidence: 99%